Culture of dental pulp stem cells on nanoporous alumina substrates modified by carbon nanotubes - Alizadeh A (Dove Medical Press, 2019)
Ameneh Alizadeh,1 Amir Razmjou,1 Mehrorang Ghaedi,2 Ramin Jannesar,3,4 Fahimeh Tabatabaei,5,6 Vahid Pezeshkpour,3,4 Lobat Tayebi5 1Department of Biotechnology, Faculty of Advanced Sciences and Technologies, University of Isfahan, Isfahan, Iran; 2Department of Chemistry, Yasouj University, Yasouj, Iran; 3Department of Pathology, Yasuj University of Medical Sciences, Yasuj, Iran; 4Department of Biotechnology and Microbial Nanotechnology, Dena Pathobiology Laboratory, Yasuj, Iran; 5Marquette University School of Dentistry, Milwaukee, WI, USA; 6Department of Dental Biomaterials, School of Dentistry, Shahid Beheshti University of Medical Sciences, Tehran, Iran Purpose: Alumina substrates are one of the commonly used scaffolds applied in cell culture, but in order to prevent formation of biofilm on the alumina substrate, these substrates are modified with carbon nanotube.Methods: The alumina substrate was made by a two-step anodization method and was then modified with carbon nanotubes by simple chemical reaction. The substrates were characterized with FTIR, SEM, EDX, 3D laser scanning digital microscope, contact angle (CA) and surface free energy (SFE). To determine how this modification influences the reduction of biofilm, biofilm of two various bacteria, Escherichia coli (E.coli) and Staphylococcus aureus (S. aureus), were investigated.Results: The biofilm on the modified substrate decreased due to the presence of carbon nanotubes and increased antibacterial properties. Dental pulp stem cells (DPSCs) were cultured onto flat alumina (FA) and nanoporous alumina-multiwalled carbon nanotubes (NAMC) substrates to examine how the chemical modification and surface topography affects growth of DPSCs. Conclusion: Cell attachment and proliferation were investigated with SEM and Presto Blue assay, and the findings show that the NAMC substrates are suitable for cell culture. Keywords: alumina scaffold, dental pulp, biofilm, adhesion, proliferation